2019
DOI: 10.3390/jcm9010003
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Heart Rate Variability and Disease Course in Multiple Sclerosis

Abstract: Little is known about the interplay between the autonomic nervous system and disease activity in multiple sclerosis (MS). We examined the relationship between heart rate variability (HRV), a reliable measure of vagal nerve function, and disease characteristics in a prospective MS cohort. Standard deviation of each normal-to-normal inter-beat interval (SDNN) and root mean square of successive differences (RMSSD), global indices of HRV, were measured in 114 MS patients, which included four predefined subgroups, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…Moreover, sympathetic reactivity can be related to plastic reserves in RRMS because patients with higher sympathetic reactivity did not show any clinical signs of ongoing brain inflammation [ 10 ] Chronic neuroinflammation may also promote the development of reduced central parasympathetic together with a suppressive role for the SNS in the CNS immune response [ 44 , 47 ] The PMS group had higher values of HFnu-dBP compared to HC; however, the age score was a significant predictor of changes for HFnu-dBP. These results suggest that proper age-matching is needed to differentiate between disease-related pathophysiology and normal aging [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, sympathetic reactivity can be related to plastic reserves in RRMS because patients with higher sympathetic reactivity did not show any clinical signs of ongoing brain inflammation [ 10 ] Chronic neuroinflammation may also promote the development of reduced central parasympathetic together with a suppressive role for the SNS in the CNS immune response [ 44 , 47 ] The PMS group had higher values of HFnu-dBP compared to HC; however, the age score was a significant predictor of changes for HFnu-dBP. These results suggest that proper age-matching is needed to differentiate between disease-related pathophysiology and normal aging [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, in our study, a more notable parasympathetic deficit was found in MS patients in exacerbation, which was attributed as a consequence of MS [ 14 ]. In contrast, the study [ 25 ] based on time-domain HRV measurements (SDNN and RMSSD) reported no difference between MS patients and HC and between predefined subgroups with various MS course.…”
Section: Discussionmentioning
confidence: 88%
“…The impairment of the parasympathetic mechanisms of the autonomic control in MS in our study was clearly seen as decreased values of time-domain HRV parameters. Correspondingly, when only a limited set of HRV characteristics, mostly the time-domain, is used, one can conclude only about the parasympathetic control of HR [ 13 , 25 ]. As for the sympathetic mechanism of the autonomic control, our study showed that it could be reliably assessed with the frequency-domain HRV analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Since greater parasympathetic cardiac activity at rest is closely related to better health, it can be observed that HRV values are higher in healthy subjects than in subjects suffering from any disease [ 6 ]. Likewise, the effects of body composition can be highlighted as a factor that may intervene in such cardiac health as seen in obese individuals [ 7 ].…”
Section: Introductionmentioning
confidence: 99%